2023
DOI: 10.1093/ofid/ofad090
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the Innate Immune Response toClostridioides difficileInfection in Hospitalized Immunocompromised Patients

Abstract: Background Clostridioides difficile infection (CDI) immune response is influenced by the innate and adaptive (humoral) immune systems. Our prior research found attenuated humoral responses to C. difficile in immunocompromised hosts (ICHs) with CDI. We sought to evaluate whether the innate immune response to CDI was influenced by ICH status. Methods We conducted a prospective study of hospitalized adults with CDI (acute diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The personal health condition significantly affects resistance against a C. difficile infection, but the infecting strain is of relevance as well (6). Different C. difficile strains are linked to divergent virulence, and various aspects such as toxin production levels or secondary bile salt resistance were shown to correlate with disease severity (7,8). However, these studies also partially contradict in the concluded relevance of specific features on virulence.…”
Section: Introductionmentioning
confidence: 99%
“…The personal health condition significantly affects resistance against a C. difficile infection, but the infecting strain is of relevance as well (6). Different C. difficile strains are linked to divergent virulence, and various aspects such as toxin production levels or secondary bile salt resistance were shown to correlate with disease severity (7,8). However, these studies also partially contradict in the concluded relevance of specific features on virulence.…”
Section: Introductionmentioning
confidence: 99%